Development of Biology Magazine (Biozine) Integrated Islamic Values in Biotechnology Materials - Hastini, Fera; Tanjung, Indayana Febriani (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2022)
The development of an integrated biology magazine of Islamic values is carried out due to the lack of available resources to study biology in the most structured schools of Islamic values.Â  The reason of this research is to develop biological magazines, test the feasibility, practicality and effectiveness of magazines. This research uses the Research and Development (R&D) method of the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The data was collected using validation sheets by media experts, material experts, Islamic values material experts, response questionnaires of biology teachers and Third class (XI) of MIA 2 MAS Al-Washliyah 22 Tembung. The result show score were 94% with a category â€œvery worthyâ€ for the media feasibility test, score of 86.5% with a category â€œvery worthyâ€ of the material feasibility test, a score of 75% with a category â€œworthyâ€ of the Islamic value material feasibility test. The practicality test scored 81% (teacher response) and 82% (student response) with â€œpracticalâ€ categories. As well as the effectiveness test got an average N-Gain score of 0.72 with a â€œhigh classificationâ€ and was effectively used